On the adhesion of sediment to footwear and the implications for geoconservation - Matthews, JJ; McIlroy, D (Springer, 2019)
The fossils at the Mistaken Point UNESCO World Heritage Site represent evidence of the oldest known, large, architecturally complex, life on Earth and are protected by the Government of Newfoundland and Labrador as part of an Ecological Reserve. Following concerns that foot traffic across the fossil surfaces was having a deleterious effect on the geoheritage, visitors were made to wear quilted ‘Bama Sokkets’ starting in 2009—though the efficacy of this management technique has never been tested. Previous studies in the materials sciences have revealed that footwear erosion of rock surfaces is primarily caused by the action of sediment between the foot and the surface; however, these findings have not before been applied to geoconservation research. In this study, we examine the adhesion of sediment to several footwear types. Our experiments reveal that under wet conditions, the ‘Bama Sokkets’ perform poorly in repelling sediment, and as such their use as a geoconservation management tool is discouraged. This study recommends the use of hydrophobic footwear for walking on geoheritage rock surfaces and has led to policy change at the Mistaken Point UNESCO World Heritage Site.